Anna K : a love story - Lee, Jenny, 1971- (Flatiron Books, 2020)
Told from multiple viewpoints, while seventeen-year-old Anna K seems above the typical problems of her Manhattan friends and siblings, finding love with a notorious playboy changes everything.